2014
DOI: 10.1590/0103-5150.027.001.ao06
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de sujeitos com doença de Parkinson e seus cuidadores

Abstract: Introdução A doença de Parkinson (DP) interfere na autonomia e independência do sujeito, afetando sua qualidade de vida (QV). Cuidadores podem ter sua QV comprometida, em função das dificuldades com o cuidado. Objetivo Avaliar e comparar a QV de sujeitos com DP e seus cuidadores e correlacionar a qualidade de vida com as características dos sujeitos. Material e métodos Foram avaliados 10 sujeitos com DP, com idade média de 65,4 anos, e 8 cuidadores, com idade média de 60,6 anos, de ambos os gêneros. Os instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 28 publications
4
9
0
21
Order By: Relevance
“…Knowing and understanding the factors that interfere in day-to-day perception improves and guides the care provided by health professionals. For patients, it is not enough to focus on the physical aspects of the disease only, but also on other dimensions, ensuring the maintenance of social relations, independence and autonomy for longer (16)(17) . The adaptation to life with PD, with the limitations and difficulties of everyday life, is revealed through the awareness of the need for better caring for one's own self (4) .…”
Section: Discussionmentioning
confidence: 99%
“…Knowing and understanding the factors that interfere in day-to-day perception improves and guides the care provided by health professionals. For patients, it is not enough to focus on the physical aspects of the disease only, but also on other dimensions, ensuring the maintenance of social relations, independence and autonomy for longer (16)(17) . The adaptation to life with PD, with the limitations and difficulties of everyday life, is revealed through the awareness of the need for better caring for one's own self (4) .…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the importance of intervention for the control of signs and symptoms of the disease, since the evaluated subscores, especially ADL, are considered important markers of PD progression (27). In addition, they suggest gain in the functional independence of these individuals, positively impacting their QoL (28).…”
Section: Discussionmentioning
confidence: 84%
“…In this sense, it is suggested that in our study the total PDQ-39 score decreased significantly, mainly due to the observed decrease in the mobility domain score. In addition, the intervention was effective for two domains related to physical aspects (mobility and bodily discomfort) commonly affected in PD (28) and for a non-motor symptom (emotional well-being), which usually plays an important role in the functionality and QoL (1).…”
Section: Discussionmentioning
confidence: 99%
“…Sendo assim verificou-se que houve uma melhora na QV sem interferir ou prejudicar nas atividades diárias habituais entre os participantes. Dados semelhantes foi percebido por outros pesquisadores 15 porém, contraditórios em outros trabalhos. 12 A ginástica laboral tem sido uma ferramenta que as empresas têm utilizado visando amenizar e reduzir problemas como índices de acidentes de trabalho e doenças ocupacionais e, que desencadeiam de forma significativa problemas de ordem econô-mica.…”
Section: Discussionunclassified